Effect of test weight of hard winter wheat on performance of finishing swine - D S Pollmann; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1982)
Ninety crossbred pigs averaging 135 lbs. were used to evaluate the effect of reduced bushel weight of wheat on performance. Wheat (59 lb) fed to finishing pigs resulted in growth and feed efficiency similar to a milo base diet. Wheat of reduced bushel weight (51 lb and 45 lb) caused a linear effect upon feed efficiency because the pigs consumed more feed per day with equal average daily gain. The blending of equal parts of milo and 45 lb wheat resulted in similar growth rate and a slightly improved feed:gain ratio as compared to the pigs fed the 45 lb wheat diet.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Hard winter wheat; Performance; Finishing pigs; Test weight